PRESSURE DISTRIBUTION AT LOWER LIMB/PROSTHETIC SOCKET INTERFACE - CHITRESH NAYAK; AMIT SINGH; HIMANSHU CHAUDHARY (International Journal of Pharma and Bio Sciences, 2016)
Artificial legs, or prostheses, are anticipated to restore a degree of normal function to amputees. Advent of digital technology for prosthetic and orthotic practice plays a significant role in the clinical treatment. Pressure is one of the most significant factors that signify the condition and tendency of the technological process used for wearing the new prosthetic. Precise interaction analysis is more critical to the achievement of the medical device industry as compared to other sectors. This current study predicts pressure distribution/ pressure measurement around the lower limb/prosthetic socket. One unilateral lower limb, below-knee amputee’s age of 48 years which was provided PTB socket with soft socks is shortlisted for participated in the current study. The pressure was measured at the below knee socket during standing. Ultra super low-pressure FUJIFILM is used with 5 to 15 microns resolution to identify pressure in range 0.2-0.6 Mpa. The method is to demonstrate and accurately measure contact pressure between thestump-socket interaction. The results revealed that the patellar tendon produced a larger pressure on the anterior side. The purpose of this study is to understand the effect of load distribution and optimization of errors during final testing over the residual limb.